Unique common fixed point results in C*-algebra valued metric spaces using (Φ-C∗)-contractions of hardy-rogers type - Mithun Paul; Kalishankar Tiwary (Journal of Hyperstructures, 2023)
In this paper we have developed C∗ -class function and introduced (Φ-C∗)-contractions of Hardy-Rogers type on C∗-algebra valued metric spaces.We have also established some unique common fixed point results for six maps in C∗-algebra valued metric spaces using this type contractions. Some basic definitions, proper-ties and lemmas are also discussed in the introduction and prelim-inaries parts. Some corollaries and examples are also given on the basis of the results.